Discourse of Littering Prohibition in Indonesia - I Dewa Putu Wijana (Journal of Pragmatics Research, 2023)
This article deals with discourses of littering prohibition signs found in various places in Indonesia, focusing on three main issues, i.e., discourse structures, pragmatic strategies, and sociocultural factors which might influence that structure and strategy. Using data collected from websites and those found in Yogyakarta Special Regency, with a socio-pragmatics approach, the research finds that littering prohibition signs are constructed by various kinds of discourse type whose complexities are formed by the sentence types and the number of sentences constructing by them. Regarding the pragmatic strategies, the signs can be delivered using non-explicit, direct, indirect, expressed, implied, literal and nonliteral strategy. Subsequently, those structures and strategies are influenced by sociocultural factors associated with the interlocutors, such as emotional condition, religious and cultural belief, education, the formality of interaction, place and time, ethnicity, age, medium of transmission, cultural entity, and political factor.       Keywords: Discourse, prohibition, strategy, and socio-pragmatics.